Priming With Silicon: A Review of a Promising Tool to Improve Micronutrient Deficiency Symptoms - Hernandez-Apaolaza, Lourdes (Frontiers in Plant Science, 2022)
Priming consists of a short pretreatment or preconditioning of seeds or seedlings with different types of primers (biological, chemical, or physical), which activates various mechanisms that improve plant vigor. In addition, stress responses are also upregulated with priming, obtaining plant phenotypes more tolerant to stress. As priming is thought to create a memory in plants, it is impairing a better resilience against stress situations. In today’s world and due to climatic change, almost all plants encounter stresses with different severity. Lots of these stresses are relevant to biotic phenomena, but lots of them are also relevant to abiotic ones. In both these two conditions, silicon application has strong and positive effects when used as a priming agent. Several Si seed priming experiments have been performed to cope with several abiotic stresses (drought, salinity, alkaline stress), and Si primers have been used in non-stress situations to increase seed or seedlings vigor, but few has been done in the field of plant recovery with Si after a stress situation, although promising results have been referenced in the scarce literature. This review pointed out that Si could be successfully used in seed priming under optimal conditions (increased seed vigor), to cope with several stresses and also to recover plants from stressful situations more rapidly, and open a promising research topic to investigate, as priming is not an expensive technique and is easy to introduce by growers.